2022
DOI: 10.3390/ijerph19148401
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and Population-Wide Interventions Are Needed to Address the Persistent Burden of Anemia among Women of Reproductive Age in Tanzania

Abstract: Recent evidence suggests that 44.8% of women of reproductive age (WRA) in Tanzania suffer from anemia. Addressing this public health challenge calls for local evidence of its burden and determinants thereof for policy and tailored interventions. This secondary data analysis used Tanzania Demographic and Health Surveys (TDHS) 2004–2005 and 2015–2016 with a total of 23,203 WRA. Data were analyzed using descriptive statistics to characterize the burden of anemia, regression analyses to examine the adjusted change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This was similar to the previous study, that AMA was a risk factor for anemia and pre-eclampsia 25 . Several studies have shown that inadequate prenatal care and the lack of professional nutrition advice during pregnancy were linked to a rise in the prevalence of anemia 26 . For the reasons mentioned above, AMA with GDM had an elevated risk of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the previous study, that AMA was a risk factor for anemia and pre-eclampsia 25 . Several studies have shown that inadequate prenatal care and the lack of professional nutrition advice during pregnancy were linked to a rise in the prevalence of anemia 26 . For the reasons mentioned above, AMA with GDM had an elevated risk of anemia.…”
Section: Discussionmentioning
confidence: 99%